Loose Panicle1 encoding a novel WRKY transcription factor, regulates panicle development, stem elongation, and seed size in foxtail millet [Setaria italica (L.) P. Beauv.] - Xiang, Jishan (PLoS One, 2017)
Panicle development is an important agronomic trait that aids in determining crop productivity. Foxtail millet and its wild ancestor green foxtail have recently been used as model systems to dissect gene functions. Here, we characterized a recessive mutant of foxtail millet, loose-panicle 1 (lp1), which showed pleiotropic phenotypes, such as a lax primary branching pattern, aberrant branch morphology, semi-dwarfism, and enlarged seed size. The loose panicle phenotype was attributed to increased panicle lengths and decreased primary branch numbers. Map-based cloning, combined with high-throughput sequencing, revealed that LP1, which encodes a novel WRKY transcription factor, is responsible for the mutant phenotype. A phylogenetic analysis revealed that LP1 belongs to the Group I WRKY subfamily, which possesses two WRKY domains (WRKY I and II). A single G-to-A transition in the fifth intron of LP1 resulted in three disorganized splicing events in mutant plants. For each of these aberrant splice variants, the normal C2H2 motif in the WRKY II domain was completely disrupted, resulting in a loss-of-function mutation. LP1 mRNA was expressed in all of the tissues examined, with higher expression levels observed in inflorescences, roots, and seeds at the grain-filling stage. A subcellular localization analysis showed that LP1 predominantly accumulated in the nucleus, which confirmed its role as a transcriptional regulator. This study provides novel insights into the roles of WRKY proteins in regulating reproductive organ development in plants and may help to develop molecular markers associated with crop yields.